The transfer of expertise to aerial skiing: Utility of an athletic profile in female athletes - Lewis, C.; Rosalie, S. M.; Gastin, P. B.; Withers, S.; Netto, K. (International Journal of Sports Science & Coaching, 2022)
Australian aerial skiers are recruited from other acrobatic sports through a nationally coordinated transition program. However, there is limited understanding of how to train transferring athletes for both optimal performance and injury prevention. The aim of this study was to test whether an athletic profile could be used to identify which skills that gymnasts possess are more and less likely to transfer to aerial skiing based on similarities and differences in the athletes` physical attributes. Six elite female aerial skiers and five state- and national-level female gymnasts completed a test protocol involving drop-landing, countermovement jump, isokinetic strength of the knee flexors and extensors, flexibility and anthropometrical profile. Aerial skiers and gymnasts had an anthropometrical profile ideal for acrobatic efficiency, but gymnasts had smaller thigh girth and greater knee range of motion. These results suggest that gymnasts are more likely to succeed in transferring to aerial skiing's acrobatic skills than skiing and landing skills. We suggest that gymnasts transferring to aerial skiing undertake pretransfer training designed to improve hamstring isometric strength and dynamic stability of the knee to reduce the risk of knee injury and improve their ability to maintain a crouched position.